The Economic Contribution to Sustainable Tourism Development in Badung Regency - Bali - Ni Made Eka Mahadewi (Institut Pariwisata dan Bisnis Internasional, 2015)
Sustainable tourism has achieved the status of being the superior goal in Badung Regency government tourism policy, and is attaining much attention in the national scientific and political discourse on tourism. Tourism is a tool that has been widely used around the world for the purpose of intensifying the economic aspects of the local community. Badung is supportive of this tool. The main objective of this paper is to unveil the potential economic benefits that can be offered by the tourism and its related activities to progressive community in Badung-Bali. Data were collected through document analyses. The qualitative studies concluded that tourism can be the impetus for sustainable development for Badung community. The benefits include enhancing their social empowerment system, strengthening their social ties and developing their social skills and relationships, increasing the income of local community, diversifying and intensifying the economic activities, providing job opportunities and alleviation of poverty. Thus, tourism has the potential to raise the consciousness of the selected community regarding sustainable development.